Do institutional investors exacerbate managerial myopia? - Wahal, Sunil; McConnell, John J (Journal of Corporate Finance, 2000)
This study analyzes corporate expenditures for property, plant and equipment (PP&E), and research and development (R&D) for over 2500 US firms from 1988 to 1994. We find no support for the contention that institutional investors cause corporate managers to behave myopically. Indeed, we document a positive relation between industry-adjusted expenditures for PP&E and R&D and the fraction of shares owned by institutional investors. This relation is robust to a variety of empirical tests, including those that account for endogeneity between institutional ownership and firm-level discretionary expenditures.